VO2MAX ANALYSIS ABC RUNNING DRILL WITH TRAINING MASK METHOD USING ANDROID BASED - Dicky Reva Apriana Sanga Dwi; Budi; Boby Agustan (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study was to analyze the effect of ABC Running Drill using Training Mask on increasing Vo2max Android-based. From the research objective, the researcher used the Pretest-Posttest Experiment Design. The research method used is the research and development (RnD) model from Borg and Gall. Population this research is beginner athletes, members of the Unit Kegiatan Mahasiwa (UKM) Track and Field STKIP Muhammadiyah Kuningan totaling 10 people, the sampling technique uses total sampling technique. The research test instrument used to collect data is the 2400 Meter run test (Cooper Test). After getting the data and obtaining it then the data is input into the system to be used as a database on the application, the android application can be downloaded link bit.ly/PDPDickyReva. To analyze the research data using SPSS Version 26, the results of the processing of the Hypothesis Test using the Pearson formula obtained the following data: There is a significant effect after the ABC Running Drill training process using the Training Mask (sig.) 0.00 < 0.05 so it can be concluded that the ABC Running exercise Drill using a Training Mask has a significant effect on increasing vo2max in Track and Field UKM STKIP Muhammadiyah Kuningan.